THE USE OF INNOVATIVE TECHNOLOGY IN TEACHING SPEAKING SKILLS TO ELEMENTARY SCHOOL TEACHER EDUCATION STUDENTS - Agus Rofii; Eva Fitriani Syarifah (Universitas Majalengka, 2024)
This research aims to explore innovative technology in teaching speaking skills to elementary school teacher education students in Universitas Majalengka such as mobile applications, computer software, and online platforms, which can be integrated effectively into the learning process to improve students’ speaking skills. This research covers aspects such as the teaching methods used, the most effective types of technology, challenges faced in implementation, and students' perceptions and responses to using technology in learning speaking skills. The research method used is qualitative research with a case study research design through classroom observation and interviews to determine the obstacles, strategies, and results of evaluations carried out by students. Participants in the research involved students in the elementary school teacher education study program. The research results show that innovative technology teaching speaking skills has various advantages. However, challenges must be overcome, such as limited access to technology, teacher readiness to integrate technology into teaching, and adapting the curriculum and relevant teaching methods. In conclusion, innovative technology in teaching speaking skills has great potential to improve students' speaking skills. However, efforts are needed to overcome technology-related challenges and ensure effective integration into the curriculum.